High Frequency Plant Regeneration of Musa paradisiaca cv. Karibale Monthan - Shashi Kumar, R.; Krishna, V.; Venkatesh, . (International Journal of Applied Sciences and Biotechnology, 2015)
High frequency plant regeneration protocol has been standardized from banana cultivar Musa paradisiaca cv. Karibale Monthan, an endemic cultivar of Malnad region of Karnataka. The fruits are used as glomerular protective to solve kidney problems. To minimize the microbial contamination and to promote healthy growth, explants were treated with 70 % absolute alcohol for 6 min, 0.1 % Mercuric chloride for 10 min and 0.2 % for 10 min, 1 % Sodium hypochlorite for 15 min, 0.1 % Cefotaxime for 5 min and 0.05 % Gentamicin for 5 min. The high frequency shoot initiation (93.33 %) was recorded at 5 mg/l BAP. The synergetic effect of BAP (4 to 6 mg/l), TDZ (0.1 to 1.2 mg/l) and coconut water (0.1 to 0.9 ml/l) induced multiple shoot buds and it was optimized at the concentration of 5 mg/l BAP, 0.5 mg/l TDZ and 0.5 ml/l coconut water with 15.90 ± 1.66 frequency of shoots per propagule. Supplementation of 1.0 mg/l IBA induced 5.33 ± 1.21 numbers of roots with a mean root length of 7.50 ± 1.87 roots. The 99% of plantlets with distinct roots and shoots were successfully acclimatized in the green house and transferred to the field to evaluate the agro-morphological variations. The weight of the bunch (kg), number of hands in a bunch, number of fingers in a hand, length of the finger (cm), girth of the finger (cm) and girth of the pseudostem (cm) exhibited by in vitro plants were higher than the in vivo plants. Int J Appl Sci Biotechnol, Vol 3(2): 202-209 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12536